PERUBAHAN PERILAKU MEMILIH MASYARAKAT PADA PEMILIHAN KEPALA DESA PINTU GOBANG KARI TAHUN 2015 - Bobby J. Yuri; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The 2015 Simultaneous Village Chief Elections is arranged by the 2014 Laws of Republic of Indenesia about Village mandates that the village head elections is implemented simultaneously within each regent/city. The village chief elections is the spearhead of democracy in community life at local level. In every leadeship election, candidate leaders always need a strategy so they can elected and win the election. This also happens at the local level such as the village. In formulating the winning strategies, the village chief candidate needs a description of the villagers voting behavior. To describe villagers voting behavior, we can use some approach of voting behavior. In this research, teh author uses polticial marketing approach that has seven cognitive indicators which affecting the villagers to make choice in the village chief election. The seven cognitive indicators are issues and policies, social imagery, emotional feelings, candidate personality, current events, personal events, and epistemic issues. The informant of this research is the villagers of Pintu Gobang Kari village who changed their choice in The 2015 Pintu Gobang Kari Village Chief Elections compared their choice in the previous election. The purpose of reseach to be achieved is to describe the causes of villagers changing voting behaviors in The 2015 Pintu Gobang Kari Village Chief Elections. The research method used is qualitative with and analyzed descriptively. The data obtained through in-depth interviews of informants detemined by the Snowball Sampling method so is desribed the cause of villagers changing voting behaviors. In the result of this research it has been described that there are some cause of villagers changing voting behaviors. First, the main cause is villager’s disappointment toward incumbent candidate during his term. The policies he took during his term makes the jealousy of villagers among hamlets. Second, every cognitive indicators of marketing approach has affect to change the villagers voting behavior. Issues and plicies with current events become dominant indicator of villagers changing voting behaviors in The 2015 Pintu Gobang Kari Village Chief Elections. Keywords: Political Marketing, Voting Behavior, Village Chief Election.